2007
DOI: 10.1007/s11104-007-9258-9
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic screen and identification of waterlogging-regulated proteins in tomato roots

Abstract: To gain a better understanding of the tomato root response to waterlogging stress at protein level, a proteomic approach has been conducted in combination with physiological analyses. Fiveweek old plants were subjected to waterlogging stress, and roots were collected 24 and 72 h after treatment. Waterlogging stress resulted in a gradual increase of lipid peroxidation and in vivo H 2 O 2 concentration in roots. To elucidate temporal changes in protein expression in tomato roots, proteins were extracted from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 66 publications
(77 reference statements)
8
59
0
2
Order By: Relevance
“…Metabolism-related proteins were found to be significantly up-or down-regulated during germination in wheat, as detected in tomato, rice and cucumber (Ahsan et al, 2007b(Ahsan et al, , 2007cDu et al, 2010). In the present study we detected differential expression of proteins involved in carbohydrate, fatty acid and amino acid metabolism.…”
Section: Metabolism-related Proteinssupporting
confidence: 59%
See 1 more Smart Citation
“…Metabolism-related proteins were found to be significantly up-or down-regulated during germination in wheat, as detected in tomato, rice and cucumber (Ahsan et al, 2007b(Ahsan et al, , 2007cDu et al, 2010). In the present study we detected differential expression of proteins involved in carbohydrate, fatty acid and amino acid metabolism.…”
Section: Metabolism-related Proteinssupporting
confidence: 59%
“…2-DE is used to investigate differentially-expressed proteins in response to abiotic or biotic stresses such as heavy metals (Ahsan et al, 2007a(Ahsan et al, , 2007c, herbicides (Ahsan et al, 2008;Castro et al, 2005;Lin et al, 2008), flooding (Ahsan et al, 2007b;Kong et al, 2010), salt stress (Du et al, 2010), chilling , ovine saliva , Meloidogyne incognita (de Deus Barbosa, 2009) and pathogens (Lee, 2006). It is well-documented that the germination process is highly disturbed by heavy metals (Xu et al, 2009), herbicides (Song et al, 2007) and antibiotics (Jin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic studies on plants exposed to low oxygen stress have shown that, in addition to the expression of classical anaerobic proteins (ANPs), there is also expression of proteins related to other mechanisms, such as reactive oxygen species (ROS) scavengers and protein synthesis in wheat (Kong et al, 2010), heat stress response in soybean (Hashiguchi et al, 2009), intracellular trafficking in maize (Chang et al, 2000), gibberellin biosynthesis, heme biosynthesis, and cell wall degradation in tomatoes (Ahsan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Dramatic changes in protein synthesis have been reported in plant roots during anaerobiosis. Most of these anaerobic proteins (ANPs) have been identifi ed as enzymes of glycolysis or sugar phosphate metabolism (Sachs et al 1996;Ahsan et al 2007a). ANPs that are part of other metabolic processes have also been reported (Chang et al 2000;Shi et al 2008).…”
Section: Introductionmentioning
confidence: 99%